History of Wilsons Mills, Maine and the Magalloway Settlements /. ([Place of publication not identified] : Town of Wilsons Mills, Maine, 1975)
While this was originally intended to be the history of Lincoln Plantation, or Wilsons Mills, it was soon apparent that the history of the Magalloway Settlements was so interwoven, one with another, that the others should be included too. There are only three settlements the length of the Magalloway River; Wentworth Location, Magalloway Plt. and Wilsons Mills. Of these three, Wentworth Location gave up its charter some years ago and is once again an unorganized township. Magalloway has unfortunately lost most of their old town records and church records by fires. So we have included in this book what information we could find on Magalloway and Wentworth Location in the old days and have asked any of the residents who wished, to add their family histories to ours. In June, 1923, Wentworth Location and Wilsons Mills joined Magalloway to celebrate Magalloway's 100th birthday.
Keywords: Wilsons Mills, Maine - History; Magalloway Plantation, Maine - History; Wentworth Location, Maine - History